Advertising and pricing strategies for the manufacturer in the presence of brown and green products. Issue 4 (29th June 2021) - Shi, Dan; Zhang, Weijia; Zou, Guangyu; Ping, Jinkun
Abstract : Purpose: The purpose of this paper is to explore the operation strategies of a manufacturer who produces brown and green product simultaneously. Design/methodology/approach: The authors establish three models to examine the joint decisions of pricing and advertising. Three advertising strategies are: non-advertising investment (NA), advertising investment for brown product (BA) and advertising investment for green product (GA). Findings: The theoretical analysis shows that advertising investment can substantially increase the product greening level and manufacturer's profit. More importantly, we find that the GA strategy is more likely to be the best strategy as the advertising investment efficiency increases. The BA strategy is more likely to be preferred as the R&D cost increases. Finally, the modeling results are verified by numerical experiments, and more insights are obtained. Research limitations/implications: This paper considers the case in which a single manufacturer produces the brown and green product simultaneously. In fact, many manufacturers in the market produce brown and green product at the same time. Furthermore, in addition to advertising investment for brown product and green product, manufacturers can also invest in advertising for brands. Originality/value: The paper contributes to the investigations on green production and advertising decisions of a manufacturer who produces brown and green products simultaneously.